Analysis OF The Incidence Of Stunting In Toddlers In The Seginim Health Centre Working Area, South Bengkulu Regency - Octavia, Hery; Nurdan, Jon Hendri; Darmawansyah, Darmawansyah (Universitas Dehasen Bengkulu, 2023)
The data from WHO, the prevalence of stunting in 2022 is 33.6%. The prevalence of stunting in Asia in 2022 is 33.0%. SSGI data on the prevalence of stunting in Indonesia in 2022 is 21.6%, this figure is still above the standard of 20%. SSGI data of Bengkulu Province in 2022, the prevalence of stunting is 19.8%, this figure is not in accordance with the target that has been set at 18.84%. South Bengkulu Regency is one of the regency that has experienced an increase in the stunting prevalence rate from 20.8% to 23.2%. Stunting data at Seginim Health Center increases in every year. The aim of the research is to analyze the incidence of stunting among toddlers in the working area of Seginim Health Center, South Bengkulu Regency. This research is a quantitative research using a cross sectional study design. The number of samples in the study was 78 respondents. The sampling technique used Simple Random Sampling. The analysis used is univariate and bivariate analysis with the chi-square test. The research results showed that a small portion of respondents experienced stunting at 29.5%, the majority of respondents had sufficient knowledge at 51.3%, a small portion of respondents had income < minimum wage at 23.1%, almost half of the respondents did not breastfeed exclusively at 42.3%. There is a significant correlation between knowledge (p=0.000), income (p=0.002), infectious diseases (p=0.007) and the incidence of stunting at Seginim Health Center, South Bengkulu. It is hoped that further research can be carried out to look at other risk factors using more in-depth research design and analysis.